Method for removing heavy metals in waste salt

Through the composite material of nano-molybdenum disulfide and weak acid-type chelating resin, the problem of insufficient removal efficiency and stability of heavy metals in waste salts is solved, and efficient adsorption and removal of trace heavy metals is achieved, which is suitable for industrial applications.

CN119503840APending Publication Date: 2025-02-25SHANXI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411517721.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art lacks efficiency and stability in the removal of heavy metals in waste salts, especially the adsorption efficiency and adsorption capacity of trace heavy metals still need to be improved.

Method used

Using nanomolybdenum disulfide-resin composite materials, the composite material is formed by combining nanomolybdenum disulfide with a weak acid-type chelating resin with iminoglyoxylic acid functional groups to adsorb heavy metals from waste salts.

Benefits of technology

It realizes efficient adsorption and removal of trace heavy metals, improves the stability and reusability of materials, simplifies the process flow, and is suitable for large-scale industrial promotion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503840A_ABST
    Figure CN119503840A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of waste salt treatment, in particular to a method for removing heavy metal in waste salt. The method is realized by preparing the nano molybdenum disulfide-resin composite material. According to the composite material, resin serves as a carrier, and nano molybdenum disulfide is stably attached to the interior and the surface of the carrier. The preparation method of the composite material comprises the following steps: (1) taking resin, and sequentially carrying out salt soaking, acid pickling, water washing, alkali washing and water washing treatment; (2) drying the resin in the step (1), and cooling to normal temperature for later use; (3) dissolving a molybdenum source and a sulfur source in deionized water, and carrying out ultrasonic treatment to obtain a mixed solution; and (4) adding the resin treated in the step (2) into the mixed solution in the step (3) to react, cooling the reaction solution to room temperature after the reaction is ended, washing and drying to obtain the nano molybdenum disulfide-resin composite material. The method has more efficient and lasting adsorption removal performance on trace metal ions and other heavy metal pollutants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waste salt treatment, and in particular to a method for removing heavy metals in waste salt. Background Art

[0002] Chemical waste salt has a large output and complex components, and contains pollutants such as organic matter and heavy metals. The more mature process for waste salt resource utilization is to pyrolyze the waste salt, and finally obtain the salt product after salt separation and crystallization. However, there are still heavy metal residues in the waste salt after high-temperature pyrolysis, which affects the treatment efficiency of subsequent processes and reduces the purity of the salt product. Therefore, the waste salt needs to be deeply purified. The adsorption method is widely used in environmental protection, chemical industry, medicine and food industry due to its advantages of simple operation, high efficiency and no energy input in the adsorption process. Traditional adsorbents include activated carbon, molecular sieves, silica gel, resins, etc. These adsorbents have a large specific surface area and rich pore structure, which can adsorb and fix the target substance. Among them, adsorption resin is an adsorbent widely used in actual wastewater treatment, pharmaceutical separation and purification. Because the resin has a high level of separation and purification and can be used repeatedly, it has been widely used in various industries. The mechanism of resin adsorption is to separate and purify the target substance through ion exchange or affinity adsorption. However, the adsorption efficiency and adsorption capacity of traditional resins for trace heavy metals still need to be improved. Nano-molybdenum disulfide (MoS2) has a layered structure similar to graphene, with weaker van der Waals forces between layers. In the stable 2H crystal form, each layer unit is a "sandwich" structure of S-Mo-S, which can provide a channel for heavy metal adsorption. Although MoS2 nanomaterials have the characteristics of high adsorption capacity and high selectivity, MoS2 is a powdery material, and the adsorption process is prone to agglomeration and dissolution, which affects its practical application. Loading molybdenum disulfide on a resin material is one way.

[0003] For example, patent CN106238015A discloses a magnetite / molybdenum disulfide water treatment material, comprising the following weight components: 20-30 parts of macroporous resin, 25-30 parts of fumaric acid resin, 5-8 parts of magnetite, 6-9 parts of molybdenum disulfide, 10-15 parts of 4-methyl salicylic acid, 5-10 parts of oxidized polypropylene wax, 3-6 parts of styrene rubber, 8-12 parts of 4-chloro-2-nitrobenzene methyl ether, 3-5 parts of sodium bicarbonate, 6-10 parts of allyl isothiocyanate, 2-5 parts of benzamide, and 1-3 parts of dithiopropanol. Although the water treatment material has a good adsorption effect on heavy metal substances, especially nickel ions and zinc ions in wastewater treatment, and the treatment time is fast and the service life is long, the water treatment material contains many ingredients, which is not the best choice in terms of economic benefits, and MoS2 and magnetite can achieve the effect of treating wastewater.

[0004] For example, patent CN115672253A discloses a high-stability molybdenum disulfide coating composite adsorbent and its preparation method and application. The adsorbent uses high molecular polymer resin microspheres as carriers, polyphenol binders as adhesion interface intermediate layers, and molybdenum disulfide nanoparticles are stably fixed on the outer surface of the carrier. High molecular polymer resin microspheres include but are not limited to various types of polystyrene or acrylic polymer skeleton resins. Functional groups with different electrical properties such as amino groups and sulfonic acid groups can be modified on the resin skeleton as needed, and the resin microspheres are spheres with a particle size of 100-1000 μm. The strong adhesion intermediate layer constructed by the polyphenol binder stably fixes the nano molybdenum disulfide on the high molecular polymer resin microspheres. This invention not only solves the technical bottlenecks such as the easy agglomeration and difficulty in solid-liquid separation of nano-scale molybdenum disulfide powder in practical applications, but also combines the polymer resin microsphere carrier with the nano molybdenum disulfide having excellent adsorption effect on pollutants. However, the invention still needs to add polyphenol binder to make MoS2 stably attached to the resin, and the binder itself does not contribute to the adsorption effect, which inevitably causes waste. Moreover, the patent only studies the application in the treatment of wastewater containing heavy metal lead and cationic dyes, but the wastewater also contains Mn and Cu, which are harmful to the body.

[0005] Therefore, there is an urgent need to develop a method for removing heavy metals from waste salt that has simple ingredients, high selectivity for heavy metals, high stability and good adsorption effect. Summary of the invention

[0006] Based on the existing deficiencies, the present invention aims to provide a method for removing heavy metals from waste salt, which has simple ingredients, high selectivity for heavy metals, high stability and good adsorption effect.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] The present invention provides a method for removing heavy metals from waste salt. The method is achieved by adsorbing and removing heavy metals from waste salt using a composite material, wherein the composite material is a nano molybdenum disulfide-resin composite material; the resin is a weak acid chelating resin with an iminooxalic acid functional group and has a diameter of 0.3-1 mm.

[0009] Preferably, the chelating resin is Amberlite IRC748 chelating resin provided by Maclean Co., Ltd. The chelating resin is a chelating resin that achieves heavy metal adsorption performance by chemically combining iminodiacetic acid functional groups with styrene-divinylbenzene in a macroreticular resin.

[0010] The preparation method of the nano molybdenum disulfide-resin composite material comprises the following steps:

[0011] (1) soaking the resin in salt solution, acid leaching, rinsing with deionized water until the effluent is neutral, alkali leaching, and rinsing with deionized water until the effluent is neutral;

[0012] (2) drying the resin washed in step (1), cooling it to room temperature, and setting it aside;

[0013] (3) dissolving the sulfur source and the molybdenum source in deionized water and performing ultrasonication to obtain a mixed solution;

[0014] (4) adding the resin treated in step (2) to the mixed solution in step (3) to carry out a reaction, and after the reaction is completed, cooling the reaction solution to room temperature, rinsing, and drying to obtain a nano-molybdenum disulfide-resin composite material.

[0015] Preferably, the salt solution in step (1) is sodium chloride, and the sodium chloride solution is 10%.

[0016] Preferably, the resin in step (1) is immersed in the sodium chloride solution for 18-24 hours, more preferably for 20 hours.

[0017] Preferably, the acid in step (1) is HCl, and the concentration of HCl is 5%.

[0018] Preferably, the base in step (1) is NaOH, and the concentration of NaOH is 4%.

[0019] Preferably, the immersion time in step (1) is 1-10 hours, more preferably 4 hours.

[0020] Preferably, the drying temperature in step (2) is 40-80°C, more preferably 60°C.

[0021] Preferably, the drying time in step (2) is 12-48 hours, more preferably 24 hours.

[0022] Preferably, the molar ratio of the sulfur source and the molybdenum source in step (3) when dissolved in deionized water is 5-50mmol:1-10mmol, and more preferably, the molar ratio is 5:1.

[0023] Preferably, the molar volume ratio of the sulfur source, molybdenum source and deionized water in step (3) is 5-50mmol:1-10mmol:10-50mL. More preferably, the molar volume ratio of the sulfur source, molybdenum source and deionized water is 25mmol:5mmol:30mL.

[0024] Preferably, the sulfur source in step (3) is selected from thiourea and thioacetamide, and more preferably thiourea.

[0025] Preferably, the molybdenum source in step (3) is selected from sodium molybdate dihydrate and ammonium molybdate tetrahydrate, and more preferably sodium molybdate dihydrate.

[0026] Preferably, the ultrasonication in step (3) is performed for 10-60 min, at a temperature of 20-60° C. and at a power of 120-300 W.

[0027] More preferably, the ultrasonication in step (3) is performed for 30 min, at a temperature of 40° C. and at a power of 300 W.

[0028] Preferably, the mass molar ratio of the resin to the sulfur source and the molybdenum source in step (4) is 1-20 g: 5-50 mmol: 1-10 mmol.

[0029] More preferably, the mass molar ratio of the resin to the sulfur source and the molybdenum source in step (4) is 5g:25mmol:5mmol.

[0030] Preferably, the reactor in step (4) is a homogeneous reactor.

[0031] Preferably, the parameters set in the reactor in step (4) are a heating rate of 5°C / min, a reaction temperature of 200°C, and a reaction time of 24h.

[0032] Preferably, the rinse agents for repeated rinsing in step (4) are methanol and deionized water.

[0033] Preferably, the drying temperature in step (4) is 20-80°C, more preferably 60°C.

[0034] Preferably, the drying time in step (4) is 24 hours.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] (1) Simple, easy to operate, and easy to promote on a large scale in industry. The composite material used is prepared by a hydrothermal one-pot method, and the material is optimized and the synthetic properties of the material are regulated by selecting sulfur and molybdenum sources and using different ratios.

[0037] (2) The nano-molybdenum disulfide and the resin material in the composite material provided work together to increase the adsorption efficiency and adsorption capacity of trace heavy metals. The nano-molybdenum disulfide increases the specific surface area and adsorption sites of the material, promoting the adsorption of trace heavy metals by the material; the resin material improves the dispersion of molybdenum disulfide, reduces the agglomeration and loss of molybdenum disulfide, and increases the stability and reusability of the material.

[0038] (3) The nano-MoS2 is evenly distributed in the composite material. Compared with MoS2 alone, its microscopic interlayer spacing is increased, which reduces the steric hindrance of heavy metals and promotes the adsorption of heavy metal ions. The composite material has more efficient and lasting adsorption and removal performance for trace Mn, Cu, Tb ions and other heavy metal pollutants. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] The data of the MoS2 / IRC748 resin composite materials in the following figures are all prepared according to the components and preparation method of Example 1.

[0040] Figure 1 This is a SEM image of the nano-molybdenum disulfide-resin composite material of the present invention;

[0041] Among them, Figure (a) (c) shows the surface of IRC748 resin alone and MoS2 / IRC748 resin composite material; Figure (b) (d) shows the surface enlarged image of IRC748 resin alone and MoS2 / IRC748 resin composite material.

[0042] Figure 2 FTIR spectrum of the nano-molybdenum disulfide / resin composite material of the present invention;

[0043] Among them, 748M5 represents composite material and 748 represents IRC748 resin.

[0044] Figure 3 The XRD spectrum of the nano-molybdenum disulfide / resin composite material of the present invention;

[0045] Among them, 748M5 represents composite material and 748 represents IRC748 resin.

[0046] Figure 4 Comparison diagram of the resin material alone and the nano-molybdenum disulfide / resin composite material of the present invention;

[0047] Among them, 748M5 represents composite material and 748 represents IRC748 resin.

[0048] Figure 5 Adsorption of Mn ions (initial concentration is 50 ppm) by the nano-molybdenum disulfide / resin composite material of the present invention;

[0049] Among them, 748M5 represents composite material and 748 represents IRC748 resin.

[0050] Figure 6 Adsorption of Mn ions (initial concentration is 4 ppm) by the nano-molybdenum disulfide / resin composite material of the present invention;

[0051] Among them, 748M5 represents composite material and 748 represents IRC748 resin. DETAILED DESCRIPTION

[0052] The present invention is further described in detail below in conjunction with specific embodiments. The embodiments of the present invention and comparative examples are not specifically described. The resin used is the Amberlite IRC748 chelating resin provided by Maclean Co., Ltd. This material is a chelating resin that realizes heavy metal adsorption performance by chemically combining the iminodiacetic acid functional group with the styrene-divinylbenzene matrix in the macroreticular resin. The resin diameter is between 0.3-1mm.

[0053] Example 1

[0054] The preparation method of the nano molybdenum disulfide-resin composite material specifically comprises the following steps:

[0055] Example 1

[0056] A method for preparing a nano molybdenum disulfide / resin composite material comprises the following steps:

[0057] (1) Soak 5 g of Amberlite IRC748 chelating resin in 10% sodium chloride for 20 h, then soak in 5% HCl for 4 h, rinse repeatedly with deionized water until it is close to neutral, then soak in 4% NaOH for 4 h, and rinse repeatedly with deionized water until it is close to neutral.

[0058] (2) The resin washed in step (1) was dried in an oven at 60° C. for 24 hours and then cooled to room temperature for later use.

[0059] (3) 5 mmol of sodium molybdate dihydrate and 25 mmol of thiourea were dissolved in 30 ml of deionized water, and the mixed solution was ultrasonicated for 30 min at an ultrasonic power of 300 W and an ultrasonic temperature of 40° C., and finally transferred into a reactor;

[0060] (4) Add 5 g of the treated resin to the reactor in step (3), and move the reactor into a homogeneous reactor. Set the reactor heating rate to 5°C / min, the reaction temperature to 200°C, and the reaction duration to 24 hours. Then cool to room temperature and take out. The obtained nano-resin composite material is repeatedly rinsed with methanol and deionized water, and finally dried in an oven at 60°C for 24 hours, and then cooled for use.

[0061] Example 2

[0062] The only difference from Example 1 is that in step (1), the soaking time in 8% sodium chloride is 18 hours, followed by soaking in 1% HCl for 1 hour, repeated rinsing with deionized water to near neutrality, and then soaking with 1% NaOH for 1 hour, the drying temperature in step (2) is 40° C., the drying time is 12 hours, the ultrasonic time in step (3) is 60 minutes, the ultrasonic temperature is 60° C. and the ultrasonic power is 300 W, and the other steps are consistent with Example 1.

[0063] Example 3

[0064] The only difference from Example 1 is that in step (1), the soaking time in 26% sodium chloride is 24 hours, followed by soaking in 6% HCl for 10 hours, repeated rinsing with deionized water to near neutrality, and then soaking with 5% NaOH for 10 hours, the drying temperature in step (2) is 80° C., the drying time is 48 hours, the ultrasonic time in step (3) is 10 minutes, the ultrasonic temperature is 20° C. and the ultrasonic power is 120 W, and the other steps are consistent with Example 1.

[0065] Example 4

[0066] The only difference from Example 1 is that in step (3), 1 mmol of sodium molybdate dihydrate and 50 mmol of thiourea are dissolved in 50 ml of deionized water, the mass of the resin in step (4) is 1 g, the reaction temperature is 150° C., and the reaction time is 15 h. The other steps are consistent with Example 1.

[0067] Example 5

[0068] The only difference from Example 1 is that in step (3), 1 mmol of sodium molybdate dihydrate and 5 mmol of thiourea are dissolved in 10 ml of deionized water, the mass of the resin in step (4) is 20 g, the reaction temperature is 240° C., the reaction time is 36 h, and the other steps are consistent with Example 1.

[0069] Example 6

[0070] The only difference from Example 1 is that the sulfur source and molybdenum source are different in the preparation process. The sulfur source of Example 6 is thioacetamide, and the molybdenum source is selected from ammonium molybdate tetrahydrate. The others are consistent with Example 1.

[0071] Comparative Example 1

[0072] The difference from Example 1 is that the parameters set in the homogeneous reactor are different, specifically, the heating rate is 10°C / min, the reaction temperature is 250°C, and the reaction time is 12h. The other steps are consistent with Example 1.

[0073] Comparative Example 2

[0074] The difference from Example 1 is that the resin in step (1) is soaked in deionized water for 4 hours without being soaked in a sodium chloride solution, and the subsequent steps are consistent with Example 1.

[0075] Comparative Example 3

[0076] The difference from Example 1 is that the resin is different, the resin is styrene-divinylbenzene resin D301, and the preparation method is the same as that of Example 1.

[0077] Effect test:

[0078] Each embodiment and comparative example selects Mn ions as the model pollutant, and tests the adsorption performance of the nano-molybdenum disulfide-resin composite material. The test steps are as follows: prepare 30mL of 4mg / L Mn ion solution, the solution pH is 3, and sodium chloride is 5%. Add 10mg of nano-molybdenum disulfide / resin composite material sample respectively, and the experiment is carried out on a magnetic stirring table with a speed of 400rmp. After adsorption for 180min, take 2ml of the solution and pass it through a 0.45μm filter membrane for testing. Use ICP-AES / MS instrument to measure the concentration of heavy metal ions. Specific adsorption data are shown in the table below:

[0079] Table 1 Adsorption performance of nano-MoS2-resin composite materials for manganese ions

[0080]

[0081]

[0082] Attached Figure 1-4 It can be proved that the nano-molybdenum disulfide-resin composite material was successfully synthesized.

[0083] It can be seen from Examples 1-6 that the nano-molybdenum disulfide-resin composite material Mn 2+ Maximum removal rate.

[0084] By the attached Figure 3 It can be seen that the mechanism of the enhanced adsorption effect of nano-MoS2-resin composite materials compared with single resin or single MoS2 is: the characteristic peaks of MoS2 at 13.7°, 28.6°, 32.4°, 35.9° and 43.2° correspond to the (002), (100), (102) and (006) crystal planes of hexagonal MoS2 (PDF#75-1539), respectively. According to the Bragg equation, the interlayer spacing (d(002)) of single MoS2 is 6.422nm. After loading, the interlayer spacing increases from the initial 6.4nm to 9.5nm, proving that the increased interlayer spacing of MoS2 in the nano-MoS2-resin composite material makes heavy metals easier to be adsorbed.

[0085] By the attached Figure 5 and6 It can be seen that when the initial concentration is 50ppm, after 60 minutes of adsorption, both the resin material and the nano-molybdenum disulfide-resin composite material can remove 90% of the Mn ions, but then the adsorption rate of the resin material alone is slow, and 94.1% of the Mn ions are adsorbed at 180 minutes. While for the composite material, 99.9% of the Mn ions are removed at 180 minutes. When the initial concentration is 4ppm, the adsorption efficiency of the nano-molybdenum disulfide-resin composite material for Mn ions is significantly higher than that of the resin material, and 99.8% of the Mn ions are removed at 180 minutes. Therefore, the composite material has a more efficient and lasting adsorption and removal performance for trace Mn ions and other heavy metal pollutants.

[0086] It can be seen from Comparative Example 1 that the optimal preparation conditions for the composite material are a heating rate of 5°C / min, a reaction temperature of 200°C, and a reaction duration of 24h.

[0087] It can be seen from Comparative Example 2 that adding sodium chloride to the resin during pretreatment can slow down the expansion of the resin. Without pretreatment with sodium chloride solution, the composite resin has poor adsorption effect.

[0088] It can be seen from Comparative Example 3 that the composite adsorption effect of molybdenum disulfide and styrene-divinylbenzene resin is relatively poor, and the interaction adsorption of the weak acid chelating resin with the iminooxalic acid functional group is enhanced.

[0089] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for removing heavy metals from waste salt, characterized in that: The method is achieved by adsorbing and removing heavy metals in waste salt by a composite material, wherein the composite material is a nano molybdenum disulfide-resin composite material; the resin is a weak acid chelating resin with an iminooxalic acid functional group and has a diameter of 0.3-1 mm.

2. The method according to claim 1, characterized in that The resin is Amberlite IRC748 chelating resin.

3. The method according to claim 1, characterized in that The preparation method of the nano molybdenum disulfide-resin composite material comprises the following steps: (1) soaking the resin in a salt solution, acid leaching, rinsing with deionized water until the effluent is neutral, alkali leaching, and rinsing with deionized water until the effluent is neutral; (2) drying the resin washed in step (1), cooling it to room temperature, and setting it aside; (3) dissolving the sulfur source and the molybdenum source in deionized water and performing ultrasonication to obtain a mixed solution; (4) adding the resin treated in step (2) to the mixed solution in step (3) to carry out a reaction, and after the reaction is completed, cooling the reaction solution to room temperature, rinsing, and drying to obtain a nano-molybdenum disulfide-resin composite material.

4. The method according to claim 3, characterized in that In step (1), the resin is immersed in the salt solution for 18-24 hours, the salt solution is sodium chloride, and the concentration of sodium chloride is 8-26%.

5. The method according to claim 3, characterized in that: In step (1), the acid is HCl, and the concentration of the HCl is 1-6%; the alkali is NaOH, and the concentration of the NaOH is 1-5%; and the time for the acid leaching and the alkali leaching is 1-10h.

6. The method according to claim 3, characterized in that The drying temperature in step (2) is 40-80° C., and the drying time is 12-48 hours.

7. The method according to claim 3, characterized in that The molar volume ratio of the sulfur source, molybdenum source and deionized water in step (3) is 5-50mmol:1-10mmol:10-50mL.

8. The method according to claim 5, characterized in that The mass volume ratio of the sulfur source, molybdenum source and deionized water in step (3) is 25mmol:5mmol:30mL.

9. The method according to claim 3, characterized in that: The sulfur source is selected from thiourea and thioacetamide.

10. The method according to claim 3, characterized in that: The molybdenum source is selected from one of sodium molybdate dihydrate and ammonium molybdate tetrahydrate.

11. The method according to claim 3, characterized in that The ultrasonic time in step (3) is 10-60 min, the ultrasonic temperature is 20-60° C. and the ultrasonic power is 120-300 W.

12. The method according to claim 3, characterized in that The mass molar ratio of the resin to the sulfur source and the molybdenum source in step (4) is 1-20 g: 5-50 mmol: 1-10 mmol.

13. The method according to claim 3, characterized in that The reaction temperature in step (4) is 150-240°C, the reaction time is 15-36h, and the heating rate is 5°C / min.

Citation Information

Patent Citations

  • Magnetite / molybdenum disulfide water treatment material and preparation method thereof

    CN106238015A